Promoting Sustainable and Inclusive Entrepreneurship through Technology-Enhanced Learning: Bridging Islamic Moral Economy, Social Studies, and English Language Education - Muhammad, Adamu Abubakar; Abubakar, Gaji Maiwada; Galadanci, Nafisa Kabir; Ahmad, Zubaida Yahya; Adam, Maryam (Journal of Regional Development and Technology Initiatives, 2026)
-